LIABILITAS, KAPITALISASI, DAN PROFITABILITAS TERHADAP PROBABILITAS KEBANGKRUTAN BANK - Utomo, St. Dwiarso; Setiawanta, Yulita (Jurnal Keuangan dan Perbankan, 2011)
The condition of Indonesian banking was going to collapse because of financial crisis. The impact of monetarycrisis automatically hit the banking sector. One effect of the monetary crisis in Indonesia about the end of the20th century was the collapse of a number of banks, because the banks were considered no longer feasible tocontinue the business. This research was conducted to examine the influence of NIITA, NIATTA, TETA,CDTD against bank insolvency probability. This study used a sample period of 2007 and 2008 at nationalbanking company listed at Indonesian Stock Exchange. The sampling technique in this study used purposivesampling technique, and obtained 50 companies. Regression model and overall model fit used in this studyhad the right model (at the level of significant 100%) to estimate the function of dummy variable (the probabilityof bank insolvency.) Or in other words the independent variable (NIITA, NIATTA, TETA, CDTD) jointlyhad a significant effect on the dependent variable (dummy variable bankrupt or not bankrupt although theresults showed that partially all independent variables had no significant influence.